Cytotoxicity of zinc nanoparticles fabricated by Justicia adhatoda L. on root tips of Allium cepa L.—a model approach - Taranath, T. C.; Patil, Bheemanagouda N.; Santosh, T. U.; Sharath, B. S. (Environmental science and pollution research international, 2015)
Zinc nanoparticles were synthesized using aqueous leaf extract of Justicia adhatoda L. The characterization of nanoparticles was done by ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, atomic force microscopy (AFM), and high-resolution transmission electron microscopy (HR-TEM). The characteristic absorption peak of the UV spectrum was recorded at 379 nm. The FTIR data revealed the possible biomolecules involved in bioreduction and capping of zinc nanoparticles for efficient stabilization. AFM and HR-TEM images have shown that the size of zinc nanoparticles ranges from 55 to 83 nm and they are spherical in shape. The biogenic zinc nanoparticles were evaluated for their toxic effect on mitotic chromosomes of Allium cepa as a model system. Experiments were conducted in triplicate to assay the effect of 25, 50, 75, and 100 % of zinc nanoparticles on mitotic chromosomes at an interval of 6 h duration for 24 h. The investigation revealed that the mitotic index (MI) was decreased with increased concentration of zinc nanoparticles and exposure duration. The results revealed that zinc nanoparticles have induced abnormalities like anaphase bridge formation, diagonal anaphase, C-metaphase, sticky metaphase, laggards, and sticky anaphase at different percentages and times of exposure. It is evident from the observation that mitotic cell division becomes abortive at 100 % treatment of zinc nanoparticles.